Efektivitas Standar Akuntansi Pemerintahan untuk Meningkatkan Sistem Pengendalian Internal RKA di Fakultas Kedokteran Gigi USU - Meilany Angreni; Puja Rizqy Ramadhan; Galih Supraja (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The delay in preparing the RKA is due to the long bureaucratic process and suboptimal coordination between departments, Internal control is not optimal, so there is still the potential for recording errors, budgeting that is not on target, to the risk of discrepancies in financial reports, the use of information technology to support the integration of SAP with an effective RKA system is not optimal. The research method used is a descriptive method. The results of the study state that the Implementation of Government Accounting Standards (SAP) at the Faculty of Dentistry USU has been running quite well and has a positive influence on the effectiveness of the RKA internal control system. SAP helps strengthen transparency, accountability, and efficiency in the preparation and implementation of the faculty budget. The effectiveness of SAP implementation is still hampered by human resource factors, limitations of the financial information system, and the lack of periodic evaluation of the implementation of internal control. To improve the effectiveness of internal control, continuous training, integration of digital financial systems, and the commitment of faculty leaders in the comprehensive implementation of SAP are needed. Strengthening SAP and SPI, the Faculty of Dentistry USU can realize better, transparent, and accountable financial governance in accordance with the principles of good university governance.